PERAN ORANG TUA DI ERA DIGITAL TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN - Nurlita, Nurlita; R, Marmawi; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the role of parents in the digital era in the social emotional development of children aged 5-6 years in Sebagu Village, Teluk Keramat District, Sambas Regency. The method used is descriptive method with a qualitative approach. The data source for this study were parents who had 3 children aged 5-6 years. Data collection tools through observation sheets, interview guidelines and documentation. The results of this study explained that the role of parents in the digital era on the social emotional development of children aged 5-6 years in Sebagu Village, Teluk Keramat District, Sambas Regency, namely (1) the role of parents as role models has been carried out well that is, parents provide an exemplary attitude by exemplifying how to play with peers, work together and show good empathy such as being gentle and not rude in terms of attitudes, actions or words in front of children, especially in everyday speech. (2) the role of parents as mentors, parents do habituation to children but it is still not optimal because parents do not have much time to accompany children because of busy parents who work all day. (3) the role of parents as controllers, parents have difficulty controlling children as seen by parents freeing children to play gadgets and dealing with children's emotions by giving gadgets as a substitute for the role of parents. (4) the role of parents as facilitators, parents are able to fulfill the child's facilities and infrastructure